Rapid Eye Movement Sleep Deprivation Combined With Fluoxetine Protects Against Depression-Induced Damage and Apoptosis in Rat Hippocampi via A1 Adenosine Receptor - Ju, Xuan; Wang, Shengdong; Yan, Pan; Zhu, Chunyan; Hu, Xiwen; Dong, Jiezheng; Tan, Zhonglin (Frontiers in Psychiatry, 2021)
Background: Rapid eye movement sleep deprivation (REMSD) and fluoxetine affects depression, yet the detailed molecular mechanisms were not clear. Methods: Rat depression CUS was constructed, and body weight of rats was measured. The efficacy of REMSD and fluoxetine on the pleasure experience, exploration, and cognition of rats with depression was determined by the Sucrose preference test, the open field test, and Morris water task, respectively. The effects of REMSD and fluoxetine on depression-induced damage and apoptosis in rat hippocampi were detected using hematoxylin-eosin (H&E) staining and Terminal transferase-mediated biotin dUTP nick end labeling (TUNEL). A1 Adenosine receptor content was measured by immunohistochemistry. Relative expressions of the A1 Adenosine receptor, proteins related to apoptosis (B Bcl-2-associated X protein, Bax; B-cell lymphoma 2, Bcl-2), Phosphoinositide 3-kinase (PI3K), P38 Mitogen-activated Protein Kinase (P38 MAPK), cFos, and Adenosine Deaminase RNA Specific 2 (ADAR2) were quantified by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot as needed. Results: Depression decreased rat weight. REMSD combined with fluoxetine increased body weight, prompted rat behavior, alleviated depression-induced damage, attenuated apoptosis, and promoted A1 Adenosine receptor level in rat hippocampi. Furthermore, the combined therapy upregulated expressions of A1 Adenosine receptor, Bcl-2, PI3K, but downregulated those of Bax, P38 MAPK, cFos and ADAR2 in the hippocampi of rats with depression. Conclusion: REMSD combined with fluoxetine protected rats against depression-induced damage and apoptosis in hippocampus via A1 adenosine receptor, providing a possible treatment strategy for depression.